Поверхня ліквідусу діаграми стану системи Al2O3–HfO2–Gd2O3 в області, що багата на Al2O3 - Лакиза, С.М.; Лопато, Л.М; Тищенко, Я.С.; Ткач, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
A liquidus surface for the Al2O3-rich corner of the Al2O3–HfO2–Gd2O3 system is constructed. No ternary compounds were found in the system under study. The ternary transformation point and the ternary eutectic point are discovered. The ternary eutectic Al2O3–GdAlO3–F-HfO2 exhibits the cooperative phase growing mechanism which allows one to obtain composite materials by the method of eutectic directional solidification.